2018
DOI: 10.3126/bibechana.v16i0.21645
|View full text |Cite
|
Sign up to set email alerts
|

Chaupadi during menstruation still a major community health challenge: perspective from Mid-Western Nepal

Abstract: Introduction: Menstruation, a normal physiological process in reproductive life of female still has many misconceptions. Knowledge of menstrual hygiene and menstrual sanitation practices affects the health of female. Lack of awareness on menstrual care practice is a challenge for community health. Objective: The objective of this study was to find knowledge and practice on menstrual hygiene; and perspective of Chaupadi (menstrual shed) among the reproductive age group female. Methodology: A community based mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…The number of participants ranged from 88 to 672 in the surveys. Among the studies using mixed methods (Amatya et al, 2018; Gautam, 2017; Joshi, 2015; Pandit et al, 2021; Parajuli et al, 2018; Thakuri et al, 2021; Thomson et al, 2019), interviews and focus group discussions were used to triangulate the survey. Studies using qualitative methods (Baumann, Merante, et al, 2021; Baumann, Lhaki, et al, 2021; Joshi & Maharjan, 2021; Karki & Khadka, 2019a; Khadka, 2020; Thapa et al, 2019; Wong, 2018) elicited more nuanced information on the underlying phenomena and provided critical, detailed information regarding chhaupadi .…”
Section: Resultsmentioning
confidence: 99%
“…The number of participants ranged from 88 to 672 in the surveys. Among the studies using mixed methods (Amatya et al, 2018; Gautam, 2017; Joshi, 2015; Pandit et al, 2021; Parajuli et al, 2018; Thakuri et al, 2021; Thomson et al, 2019), interviews and focus group discussions were used to triangulate the survey. Studies using qualitative methods (Baumann, Merante, et al, 2021; Baumann, Lhaki, et al, 2021; Joshi & Maharjan, 2021; Karki & Khadka, 2019a; Khadka, 2020; Thapa et al, 2019; Wong, 2018) elicited more nuanced information on the underlying phenomena and provided critical, detailed information regarding chhaupadi .…”
Section: Resultsmentioning
confidence: 99%
“…Six papers reported on age in association with menarche, dysmenorrhea, irregular menstrual bleeding and sanitary pad use [ 18 , 23 , 24 , 30 , 32 , 34 ]. Liu et al (2016) reported that the median age for women with dysmenorrhea was 26 years and with irregular menstrual bleeding was 34 years [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reported that women and girls mostly received information on menstruation from their mothers and friends [ 23 , 30 , 35 ]. The information received included restrictions and impurity associated with menstruation, cramps, how to sit to avoid stains, and how to fold and clean menstrual cloths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The practice has been described in greater detail elsewhere [25][26][27][28][29]. Briefly, the practice is rooted in patriarchy and Hindu mythology that considers women impure, thus untouchable, during menstruation and childbirth.…”
Section: Settingmentioning
confidence: 99%